Advances in Analytical Strategies to Study Cultural Heritage Samples (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint provides the most recent advancements and trends in the analysis of cultural heritage samples, including archaeological and bio-archaeological samples, confirming the growing public and academic interest in this field. The submitted papers cover different aspects of cultural and archaeological heritage protection, conservation, and restoration. The complexity of such samples, including archaeological samples, generally requires a multi-analytical approach. The integrated use of different analytical techniques, with the preference for noninvasive or micro-invasive ones, allows an in-depth understanding of the original materials and their degradation processes and helps obtain innovative solutions for the restoration and conservation of artworks.